1967
DOI: 10.1620/tjem.92.301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet on Experimental Pancreatitis in Rat

Abstract: In order to study the effect of diet on the incidence of experimental pancreatitis, ligation of the common bile duct was carried out in 179 rats which had been fed on six different types of diet for 4 to 6 months. The highest mortality rate and most marked histologic changes of the pancreas were observed in the group of high protein diet. It was assumed that the reactive pattern of the pancreas might be influenced by dietary composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…47 Animal models document associations with high protein and fat diets in the development of AP. [48][49][50][51] Further potential evidence for the role of high-fat diets in the development of AP comes from the results of a study evaluating ketogenic diets in the management of idiopathic epilepsy. 3 In that study 3/9 dogs fed a ketogenic diet (57% fat, 5.8% NFE, 25% crude protein; as dry matter) developed pancreatitis whereas only 2/31 dogs fed the control diet (16% crude fat, 54% NFE, 25% crude protein; as dry matter) developed pancreatitis.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…47 Animal models document associations with high protein and fat diets in the development of AP. [48][49][50][51] Further potential evidence for the role of high-fat diets in the development of AP comes from the results of a study evaluating ketogenic diets in the management of idiopathic epilepsy. 3 In that study 3/9 dogs fed a ketogenic diet (57% fat, 5.8% NFE, 25% crude protein; as dry matter) developed pancreatitis whereas only 2/31 dogs fed the control diet (16% crude fat, 54% NFE, 25% crude protein; as dry matter) developed pancreatitis.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…It has been consistently shown that high protein and fat diets potentiate the severity of experimentally-induced AP in animals. [131819] Contrary to the above studies, Sarles et al . [48] found that the administration of different diets to rats fed on ethanol produced changes in the pancreas no different to those fed on water.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests a role for diet in the development of AP, a role that has been investigated in animal models[13] as well as in humans. [46] On the other hand, lack of nutrition as well as malnutrition have also been linked to the development of AP.…”
mentioning
confidence: 99%
“…This is in agreement with Maki's work. 4 Another report showed a divergent result; namely that experimental acute pancreatitis was most severe in dogs that had been fed a high fat diet.3 It is worth noting that although the induction methods and animals were different in these two papers, high fat and high protein diets intensified acute pancreatitis in each case.…”
Section: Discussionmentioning
confidence: 99%